Monocyte-Derived Dendritic Cells Differentiated in the Presence of Lenalidomide Display a Semi-Mature Phenotype, Enhanced Phagocytic Capacity, and Th1 Polarization Capability - López-Relaño, Juan; Martín-Adrados, Beatriz; Real-Arévalo, Irene; Lozano-Bartolomé, Javier; Abós, Beatriz; Sánchez-Ramón, Silvia; Alonso, Bárbara; Gómez del Moral, Manuel; Martínez-Naves, Eduardo (Frontiers in Immunology, 2018)
Lenalidomide is an analogue of thalidomide, with potent anticancer activity demonstrated in several hematological malignancies. It has immunomodulatory properties, being able to enhance the activation of different types of immune cells, which results in antitumor activities. Dendritic cells (DCs) are pivotal in the immune response, and different immunotherapeutic approaches targeting these cells are being developed. Since little is known about the effect of lenalidomide on DCs, the goal of the present work was to investigate the phenotype and function of human monocyte-derived DCs differentiated in the presence of lenalidomide (L-DCs). Our results showed that L-DCs display a unique phenotype, with increased cell surface expression of some maturation markers such as CD1d, CD83, CD86, and HLA-DR. This phenotype correlates with a lower expression of the E3 ubiquitin-ligase MARCH-I in L-DCs, up-regulating the cell surface expression of CD86 and HLA-DR. In addition, immature L-DCs express higher amounts of DC-SIGN on the cell surface than control immature DCs. After LPS stimulation, production of IL-6 and TNF- was severely decreased, whereas IL-12 and IL-10 secretion was dramatically upregulated in L-DCs, compared to that in the controls. Functionally, L-DCs are more effectively recognized by NKT cells in cytotoxicity experiments. Furthermore, L-DCs display higher opsonin-independent antigen uptake capability than control DCs. Mixed lymphocyte reaction experiments showed that L-DCs could stimulate naïve CD4 T-cells, polarizing them towards a predominant Th1 phenotype. In summary, DCs derived from monocytes in the presence of lenalidomide present a semi-mature phenotype, increased phagocytic capacity, reduced production of proinflammatory cytokines, and the ability to polarize T-cells towards predominant Th1-type responses; these are qualities that might be useful in the development of new immunotherapeutic treatments. KEY WORDS: lenalidomide, dendritic cells, antigen presentation, phagocytosis, NKT cell, T-cells, cytokines